PERAN GURU PAI DALAM PENERAPAN KURIKULUM K13 PADA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS X DI SMA SWASTA WIDYA DHARMA KEC.TUREN KAB.MALANG - Septi Rahayu Maulan; Chalimatus Sa’dijah; Dwi Fitri Wiyono (VICRATINA, 2021)
Education is one of the long-term investments that aim to change human behavior. Historically, education has been one of the moral and ethical foundations in the process of forming national identity, the Government through the Ministry of Education and Culture has set a change in the KTSP curriculum to the 2013 curriculum which began in 2013/2014 to be exact on July 15, 2013 and carried out gradually every year. school. This study aims to describe how the teacher's strategies, supporting factors and inhibiting factors in implementing the 2013 curriculum in Islamic Religious Education class X at Widya Private High School. This research method is carried out using a qualitative approach based on phenomenology by using a case study research type. Based on the results of the study, it can be concluded that learning planning, learning implementation and learning assessment carried out by PAI teachers in class X SMA Swasta Widya Dharma Turen were carried out based on already implemented according to the K13 curriculum. The supporting factors are the facilities and infrastructure, the competence and quality of teachers and the contributions and activities of students, while the inhibiting factors are differences in the psychological condition and abilities of students, the need for careful preparation and improvement of the quality of teachers in implementing the K13 curriculum and the lack of access to information about the K13 curriculum..